AB1067 Golimumab Utilization Patterns and Refill Adherence in Patients with Rheumatoid Arthritis, Psoriatic Arthritis and Ankylosing Spondylitis. (10th June 2014) - Ellis, L.; Bolge, S.; Rice, P.
Abstract : Background: Golimumab (GLM) is a subcutaneous anti-TNF medication indicated once-monthly for patients with rheumatoid arthritis (RA), psoriatic arthritis (PSA), and ankylosing spondylitis (AS). Information about real-world utilization patterns is important for rheumatologists understanding about how patients take their medication. Objectives: This study reports real-world utilization patterns observed for RA, PSA, and AS patients treated with GLM. Methods: Patients with an ICD-9 code for RA, PSA, or AS receiving ≥2 fills of GLM as their first biologic medication (bionaive) or most recent biologic medication (bio-experienced) were identified between 1/1/2008 and 12/31/2010 in a large healthcare claims dataset (Truven Health). Patient characteristics and refill patterns were summarized using descriptive statistics. The proportion of adherent refills was calculated as the number of refills occurring between 21and 38 days from a previous fill divided by the total refill intervals. Results: A total of 1, 515 patients with ≥2 GLM fills and a diagnosis of RA (n=1, 036), PSA (n=325) or AS (n=154) were identified in the database. Median age was: RA 52 years; PsA 50 years; AS 47 years. The majority were bio-experienced (RA 72%; PsA 79%; AS 79%). A total of 13, 738 GLM refills were observed (RA 9, 398; PsA 2, 961; AS 1, 369). The number of refills per patient ranged from 2 to 34 with a mean (SD) of 10.1 (7.25) and median of 8. The mean (SD) interval for all refills was 34.8±13.0 days; median was 31 days. Median refill interval for RA, PsA and AS was 31 days in bio-experienced subgroups and 32 days for bionaive subgroups. The proportion of adherent refills overall was 78%; (RA 79%; PSA 76%; AS 78%). The proportion of adherent refills appeared similar for bionaive and bioexperienced patients except in the AS group (bionaive 73.8%; bioexperienced 79.3%). Conclusions: This retrospective observational study confirms earlier findings that GLM is utilized largely in patients who have used other biologic medications. A high proportion of GLM-treated patients were adherent to refilling medication and median refill intervals occurred as recommended in the GLM prescribing information. Disclosure of Interest: L. Ellis Employee of: Janssen Scientific Affairs, LLC, S. Bolge Employee of: Janssen Scientific Affairs, LLC, P. Rice Consultant for: Janssen Scientific Affairs, LLC DOI: 10.1136/annrheumdis-2014-eular.3027